2016
DOI: 10.1111/idj.12255
|View full text |Cite
|
Sign up to set email alerts
|

Association between chronic periodontitis and oral health-related quality of life in Sri Lankan adults

Abstract: Oral health-related quality of life deteriorates with the increase in severity of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
23
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 28 publications
8
23
0
1
Order By: Relevance
“…In the present study of individuals from the Bahia region of northern Brazil, the association was not statistically significant in individuals who presented with only one of the oral conditions (caries or periodontitis). This is in contrast to investigations in other countries and regions that evaluated the impact of these oral conditions on quality of life separately . In these studies, individuals with severe periodontitis reported a greater negative impact on quality of life related to oral health .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present study of individuals from the Bahia region of northern Brazil, the association was not statistically significant in individuals who presented with only one of the oral conditions (caries or periodontitis). This is in contrast to investigations in other countries and regions that evaluated the impact of these oral conditions on quality of life separately . In these studies, individuals with severe periodontitis reported a greater negative impact on quality of life related to oral health .…”
Section: Discussionmentioning
confidence: 64%
“…Studies that have evaluated the impact of oral conditions on the quality of life show that not only the presence but also the severity of caries or periodontal disease are associated with a worse oral health-related quality of life. 6,8,[13][14][15][16][17] The higher the caries experience or the severity level of periodontitis, the greater the impact on people's daily lives. 16,17 However, this research has traditionally analyzed each disease separately.…”
mentioning
confidence: 99%
“…Psychological discomfort was the most commonly reported complaint, whereas handicap was the least reported complaint. Physical pain was the most common complaint in a study conducted in Sri Lanka . In another study done in Germany, it was reported that the functional limitation was the most common impact domain .…”
Section: Discussionmentioning
confidence: 96%
“…Our results are consistent with other studies using OHIP‐14 in patients with chronic periodontitis. Physical pain was the most prevalent reported impact in a study recently conducted in China and another in Sri Lanka . Looking at a study performed in Germany, “functional limitation” was the most frequent domain reporting impairment .…”
Section: Discussionmentioning
confidence: 96%
“…assessed OHRQoL in ChP patients comparing urban with rural populations in India: The most affected subscale was psychological disability and functional limitation, respectively . Oral health perceived from different social, ethnic, and cultural background shall be an explanation for the reported differences …”
Section: Discussionmentioning
confidence: 99%